Changes in heteronormativity of the topic "Family" in the series (new) english file -Intermediate level- - Di Pietro, Paula Anabel (My University, 2023)
Heterosexuality is the only sexual orientation widely accepted in Western society while all other sexualities are generally excluded. A heteronormative community is made up of heterosexual marriage, sexual orientation with reproductive purposes and the perpetuation of heteronormative roles and stereotypes. These ideas seem to be replicated and reinforced not only in the media or advertisements, but also in the educational system, more specifically in EFL textbooks. The present work proposes to analyse the changes in heteronormativity in the units devoted to the topic of “Family” in the series (New) English File of intermediate level in its four editions (1996, 2003, 2013 and 2018). For such purpose, a qualitative research is carried out to examine the pictures and images in the light of the Barthesian myth and the texts by applying the metadiscourse theory by Hyland. Results have shown that these texts and pictures still contribute to the reproduction of the heteronormative model.

La heterosexualidad es la única orientación sexual ampliamente aceptada en la sociedad occidental, mientras que el resto de las sexualidades son generalmente excluidas. Una comunidad heteronormativa está conformada por el matrimonio heterosexual, la orientación sexual con fines reproductivos y la perpetuación de roles y estereotipos heteronormativos. Estas ideas parecen ser replicadas y reforzadas no solo en los medios de comunicación o en las publicidades, sino también en el sistema educativo, más específicamente en libros de inglés como lengua extranjera. El presente trabajo se propone analizar los cambios en la heteronormatividad en unidades dedicadas al tópico “familia” en la serie (New) English File de nivel intermedio en sus cuatro ediciones (1996, 2003, 2013 y 2018). Para tal fin, se realiza un estudio cualitativo para examinar dibujos e imágenes desde una perspectiva Barthesiana y textos al aplicar la teoría de metadiscurso de Hyland. Los resultados han demostrado que estos textos e imágenes aún contribuyen a la reproducción del modelo heteronormativo
Keywords: Heteronormativity; stereotypes; Gender; EFL textbooks; Myth; Discourse analysis.; Heteronormatividad; Estereotipos; Género; Análisis del discurso